The training manager's desktop guide - Davies, Eddie (Thorogood Pub., 2007)
Training is a vital part of professional development, but how much of the time, effort and cost invested comes back in improved performance and profitability? This title explains how to develop a coherent training strategy and then how to deliver training that produces results.